2018
DOI: 10.1017/s1368980018002938
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and related factors of schoolchildren in Çorum, Turkey

Abstract: ObjectiveWe aimed to determine nutritional status and related factors among schoolchildren in Çorum, Central Anatolia, Turkey.DesignSchoolchildren’s height and weight were measured to calculate BMI and BMI Z-scores. Height, weight and BMI Z-scores were analysed and nutritional status classified according to the WHO.SettingCentral Anatolia, Turkey.ParticipantsSchoolchildren aged 5–17 years (n 1684) participated in study.ResultsOf children, 4·2% were stunted, 6·9% thin, 13·8% overweight and 6·6% were obese. Prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
3
1
Order By: Relevance
“…26 It is worth noting that childhood and adolescence obesity is a risk factor for obesity in adulthood. 7 Results from adjusted analyses in the present study showed a statistical association between maternal BF and overweight/ obesity prevalence among schoolchildren aged 7-10 years, and between BF duration (≤ 6 months) and overweight/obesity prevalence among schoolchildren aged 7-10 years; however, such association was not found in the older group (schoolchildren aged 11-14 years). The results of this study are similar to the findings of Grube et al, who conducted a study on German children and adolescents in 2003-2006 and observed a protective effect of BF on children aged 7-10 years, although they did not find an association in other age groups (3-6, 11-13, and 14-17 years of age).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…26 It is worth noting that childhood and adolescence obesity is a risk factor for obesity in adulthood. 7 Results from adjusted analyses in the present study showed a statistical association between maternal BF and overweight/ obesity prevalence among schoolchildren aged 7-10 years, and between BF duration (≤ 6 months) and overweight/obesity prevalence among schoolchildren aged 7-10 years; however, such association was not found in the older group (schoolchildren aged 11-14 years). The results of this study are similar to the findings of Grube et al, who conducted a study on German children and adolescents in 2003-2006 and observed a protective effect of BF on children aged 7-10 years, although they did not find an association in other age groups (3-6, 11-13, and 14-17 years of age).…”
Section: Discussioncontrasting
confidence: 66%
“…5 However, the hypothesis of this protective effect remains unclear, with some studies conducted in the second half of the 2010s that verified different associations between BF or its duration and obesity. [5][6][7] Studies on this association have been carried out in Brazil, [8][9][10] particularly on elementary school students, but they were conducted using different methods regarding the definition of outcome and independent variables. Siqueira & Monteiro, in a study conducted in São Paulo in 2007, observed a twice chance of overweight/obesity in children aged 6-14 years who have never been breastfed, compared with those breastfed (dichotomic variable: breastfed vs. never breastfed).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings in a retrospective cohort of malnourished and control children revealed poor weight gain accompanied with short stature and loss of appetite as the leading symptom profile on admission in malnourished patients, while higher likelihood of younger age, shorter duration of breastfeeding, lower family monthly income and poorer maternal education in malnourished vs. control children. Notably, data from a recent study in Turkish children indicated lower birth weight and shorter breast-feeding duration in children with stunting and underweight than those with normal or taller height and normal weight or overweight/obesity, respectively 18 . In addition, data from Eastern Turkey revealed association of low monthly family income and educational level, prematurity and unemployed father with increased risk of malnutrition, with no significant relationship between malnutrition and gender 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, we feature articles on nutrition in children and adolescents from around the word, encompassing both undernutrition in India ( 1 ) , Bangladesh ( 2 ) , Iran ( 3 ) and Turkey ( 4 ) and overnutrition in Brazil ( 5 , 6 ) . One article ( 7 ) reports on the prevalence of anaemia and stunting in 193 065 children aged 6–59 months in forty-three low- and middle-income countries using data from Demographic and Health Surveys during the period 2005–2015.…”
mentioning
confidence: 99%